Loneliness and health of older adults: The role of cultural heritage and relationship quality - Elizabeth J. Casabianca; Matija Kovacic (European Commission, 2022)
We estimate the direct causal effect of loneliness on a variety of health outcomes using a sample of second-generation immigrants among older adults drawn from the Survey of Health, Ageing and Retirement in Europe. In an effort to account for the endogeneity of self-declared loneliness, we explore the link between loneliness and a specific trait of maternal cultural background strongly associated with quality of relations and use the latter as an instrument for loneliness. We thus also assess the importance of cultural heritage in shaping individuals' perceptions of loneliness. Additionally, we investigate one pathway by which some specific ancestral factors may influence the formation of cultural traits in the modern era. Our results suggest that loneliness has a significant impact on health, both mental and physical. Notably, our identification strategy allows us to uncover a larger effect of loneliness on health than that found in an OLS setting. These findings are robust to a battery of sensitivity checks.
Keywords: I12; I14; J14; D91; Z13; 330; Loneliness; relationship quality; culture; mental health; physical health